Building a cost-effective, fault-tolerant, and hardened onprem infrastructure with IaaS for disaster resiliency - Ampoloquio, Jason M. (Animo Repository, 2023)
Information and Communication Technology (ICT) has become a critical service enabler in today's government. When implemented correctly, it simplifies operations, creates a more agile workforce, and enables seamless and effortless transactions with the government. Maintaining and maximizing the value of ICT systems and keeping them secure from evolving cyber threats requires particular skills and experience, which government agencies struggle with in most cases. A disruption of mission-critical applications can be catastrophic to an organization that depends heavily on the availability of these systems to run its day-to-day operations and provide services. To ensure public service continuity in both foreseeable and unforeseeable events or disasters, whether artificial or natural, it is paramount that mission-critical applications are designed and built with security, fault-tolerance, and disaster recovery capabilities from the beginning rather than as an afterthought. This capstone project examines existing security standards, hardening practices, provisioning tools, and configuration management technologies that can be applied to rebuild the Insurance Commission website and agents' computerized examination system with security, fault-tolerance, and disaster resiliency in mind. Keywords: Blue-Green architecture, Disaster Resiliency, Configuration Management